Animal Cancer Trust. (2nd May 2022) - Adams, Vicki
Abstract : The Animal Cancer Trust aims to be the first port of call for owners of pets with cancer, and their veterinary surgeons and nurses. Chief executive and veterinary epidemiologist Vicki Adams explains what the charity does and how you can get involved.